2021
DOI: 10.1038/s41419-021-03907-1
|View full text |Cite
|
Sign up to set email alerts
|

Clobetasol promotes neuromuscular plasticity in mice after motoneuronal loss via sonic hedgehog signaling, immunomodulation and metabolic rebalancing

Abstract: Motoneuronal loss is the main feature of amyotrophic lateral sclerosis, although pathogenesis is extremely complex involving both neural and muscle cells. In order to translationally engage the sonic hedgehog pathway, which is a promising target for neural regeneration, recent studies have reported on the neuroprotective effects of clobetasol, an FDA-approved glucocorticoid, able to activate this pathway via smoothened. Herein we sought to examine functional, cellular, and metabolic effects of clobetasol in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Previous clinical studies have demonstrated that brain levels of NAA in patients with ALS are significantly lower than those of healthy subjects [ 26 , 27 , 28 ] and correlates negatively with time of patients’ survival [ 29 ]. Furthermore, in a mouse model of selective motoneuronal loss, mimicking the primary pathology associated with ALS, we have very recently found a dramatic depletion of NAA in spinal cord extracts [ 30 ]. It has been shown that changes in cerebral NAA levels under pathological conditions are not simply due to neuronal loss but may also occur under conditions of mitochondrial dysfunction with consequent energy penalty [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have demonstrated that brain levels of NAA in patients with ALS are significantly lower than those of healthy subjects [ 26 , 27 , 28 ] and correlates negatively with time of patients’ survival [ 29 ]. Furthermore, in a mouse model of selective motoneuronal loss, mimicking the primary pathology associated with ALS, we have very recently found a dramatic depletion of NAA in spinal cord extracts [ 30 ]. It has been shown that changes in cerebral NAA levels under pathological conditions are not simply due to neuronal loss but may also occur under conditions of mitochondrial dysfunction with consequent energy penalty [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds, particularly uric acid, represent the end products of the adenine nucleotide degradation pathway occurring at a high rate under conditions of impaired energy metabolism, i.e., when imbalance between ATP production and consumption takes place [ 36 , 37 ]. Increased oxypurines have been observed during coronary bypass surgery [ 38 ], following traumatic brain injury [ 39 ], in patients affected by multiple sclerosis (correlating with disease progression, clinical subtype and neuroradiological findings) [ 40 , 41 ], as well as under various experimental conditions of cellular energy penalty [ 42 , 43 , 44 ] including those found in muscle tissue in an ALS-like murine model of motoneuron ablation [ 30 ]. Recently, using 31 P-magnetic resonance spectroscopy for the quantification of energy-related metabolites in vivo, it has been found that patients with ALS have evident mitochondrial dysfunction in both brain and muscle tissues [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were counterstained with Mayer’s hematoxylin (Bio-Optica, Milan, Italy), dehydrated with increasing concentrations of ethanol (50%, 70%, 95%, 100%) and xylene, and cover-slipped with Entellan (Merck Millipore, Cat.No. 1.079.600.500) [ 48 ]. Digital images were acquired using the Nexcope NIB600 biological microscope.…”
Section: Methodsmentioning
confidence: 99%
“…2 E). In order to more intuitively evaluate the Gli1 nuclear translocation, cell immunofluorescence staining of Gli1 was performed as previous studies [ 35 , 36 ]. The results indicated that Gli1 expression was obviously upregulated in the 0 µg/cm 2 group in both cytoplasm and nucleus.…”
Section: Resultsmentioning
confidence: 99%